Experiences of HIV/AIDS home-based caregivers in Vhembe district of the Limpopo Province - N.S. Mashau; M. Davhana-Maselesele (AOSIS, 2009)
The purpose of this study was to explore and describe the experiences of HIV and AIDS home-based caregivers in the Vhembe district of Limpopo Province. A qualitative research design which was exploratory, descriptive and contextual was executed with a sample of purposively selected participants who provided home-based care to people living with HIV and AIDS in the Vhembe district of Limpopo Province. Data saturation occurred after in-depth interviews with fifteen participants. In-depth individual interviews and field notes were also used during data collection. The findings reveal that HIV/AIDS home-based caregivers express pain and despair when caring for HIV/AIDS patients. The theme was supported by the following categories and subcategories: problems related to stigma when caring for patients at their homes; stress, burnout, frustration and feelings of helplessness when caring for patients. Recommendations that are described focus on building a working relationship between the home-based caregivers, community and the family.